A study of relationship between working environment and employees’ productivity Majlis Perbandaran Kluang / Siti Aisyah Mohd Isa - Mohd Isa, Siti Aisyah (Faculty of Business and Management, 2018)
This study is to study the impact of working environment on employees’ productivity. Four objective have been determined to achieve the purpose of this research. The first objective is to investigate the relationship between good relation with co-worker and employee productivity, the second objective is to investigate the relationship between supervisor support and employees’ productivity. The third objective is to investigate the relationship between adequate workload and employees’ productivity. Lastly the fourth objective is to find out which factor have the most impact on employees’ productivity. For this research the target population is the employees of Majlis Perbandaran Kluang with the total of 250 employees located in Wisma Majlis Perbandaran Kluang. The sample size chosen for this research is 152 and out of 152 questionnaire being distributed only 140 were return and is used for this study. To analyze the data descriptive, correlation, and Pearson analysis was used. Hence the result from this study shows good relation with co-worker and supervisor support shows that there is a positive and significant relationship with employees’ productivity. However there is no significant relationship between adequate work load and employees’ productivity. Supervisor support result shows that it the most influence factor on employees’ productivity.